Knowledge, attitude, barriers, professional behaviour and possible interventions: a survey on healthcareassociated infections among the healthcare workers of an intensive care unit in a large teaching hospital in Rome - Angelozzi, A.; Caminada, S.; Dorelli, B.; Sindoni, A.; Baccolini, V.; Di Paolo, C.; Mele, A.; Salvatori, L. M.; Alessandri, F.; Marzuillo, C.; De Vito, C.; Tellan, G.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Healthcare-associated infections are the main complications of hospitalization. A bottom-up approach, where the Healthcare workers involved play a key role, can be adopted to limit the Healthcareassociated infections burden. To this end, a survey was conducted in the main intensive care unit of Umberto I Teaching Hospital of Rome, where an active surveillance system has been in place since April 2016. Methods. A questionnaire of 36 questions was developed and administered to assess socio-occupational characteristics, knowledge of Healthcare-associated infections, attitudes and barriers encountered in compliance with hygiene standards, self-analysis of professional behaviour, and proposals for new interventions. Variables were evaluated by univariate analysis, and multivariable logistic regression models were constructed to identify predictors of adequate knowledge, positive attitude and appropriate professional behaviour. Results. Overall, 79/89 Healthcare workers completed the questionnaire. Multivariate analysis showed that Healthcare workers, who participated in ward meetings to share active surveillance reports, were more likely to have adequate knowledge (aOR=4.21, 95% CI: 1.36-13.07). Only job type seemed to be a predictor of adequate behaviour, since nurses and physicians were more likely to show adequate behaviour than residents in training (aOR=0.21, 95% CI: 0.06-0.74). Direct observation of compliance with standard hygiene precautions and the identification of ‘local champions’ to manage Healthcare-associated infections’ issues were the most requested interventions.Conclusions. Our study suggests that the training of healthcare professionals is a key factor in preventing and containing the spreading of Healthcare-associated infections. Moreover, by encouraging greater Healthcare workers’ involvement, we conclude that a bottom-up approach is likely to improve Healthcare-associated infections’ prevention and management.